Clear and Simple as the Truth: Writing Classic Prose (Second Edition) - Barlow, Dudley (The Education digest, 2011)
For more than a decade, Clear and Simple as the Truth has guided readers to consider style not as an elegant accessory of effective prose but as its very heart. Francis-Noël Thomas and Mark Turner present writing as an intellectual activity, not a passive application of verbal skills.